1994
DOI: 10.1128/aem.60.11.4142-4147.1994
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Oleuropein by Lactobacillus plantarum Strains Associated with Olive Fermentation

Abstract: Oleuropein (Chemical Abstracts Service registry number 32619-42-4), a bitter-tasting secoiridoid glucoside commonly found in leaves of the olive tree as well as in olives (Olea europaea L.), was found to be hydrolyzed by the j-glucosidase (EC 3.2.1.2.1) produced by oleuropeinolytic LactobaciUlus plantarum-type strains. Three strains, designated B17, B20, and B21, were isolated from the brine of naturally ripe olives not treated with alkali. These strains were rod-shaped forms, grown at a pH 3.5 limit, and tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(57 citation statements)
references
References 22 publications
1
54
0
2
Order By: Relevance
“…The evaluation of ORAC was conducted on some olive oil pure phenolic compounds and free fatty acids. The phenolic compounds used were: caffeic acid (Merck, Darmstadt, Germany), gallic acid (Merck), oleuropein (Extransynthese, Genay, France), aglycon [10] and hydroxytyrosol (Cayman, MI, USA). The free fatty acids used were oleic acid (Fluka, Buchs, Switzerland), stearic acid (Fluka), palmitic acid (Fluka) and linoleic acid (Fluka).…”
Section: Determination Of Orac Of Pure Olive Oil Compoundsmentioning
confidence: 99%
“…The evaluation of ORAC was conducted on some olive oil pure phenolic compounds and free fatty acids. The phenolic compounds used were: caffeic acid (Merck, Darmstadt, Germany), gallic acid (Merck), oleuropein (Extransynthese, Genay, France), aglycon [10] and hydroxytyrosol (Cayman, MI, USA). The free fatty acids used were oleic acid (Fluka, Buchs, Switzerland), stearic acid (Fluka), palmitic acid (Fluka) and linoleic acid (Fluka).…”
Section: Determination Of Orac Of Pure Olive Oil Compoundsmentioning
confidence: 99%
“…Several research groups have reported that strains of Lactobacillus plantarum (Ciafardini et al, 1994) and Lactobacillus pentosus (Servili et al, 2006) are able to degrade the bitter glucoside oleuropein and it was assumed that these lactic acid bacteria (LAB), which are responsible for a proper olive fermentation, produce the enzyme ß-glucosidase during olive brining that catalyses the rupture of the glycosidic bond of the oleuropein moiety (Ciafardini & Zullo, 2000).…”
mentioning
confidence: 99%
“…Hydroxytyrosol originates from acidic hydrolysis of oleuropein as suggested by Brenes et al (1993) . In this case, there was no lactic acid formation during storage and hydrolysis of oleuropein could not be due to the enzymatic activity of lactic acid bacteria (Ciafardini et al, 1994).…”
Section: Chemical Characteristics Of Storage Liquidsmentioning
confidence: 74%